Cover Feature: Understanding the Colloidal Stability of Nanoparticle–Ligand Complexes: Design, Synthesis, and Structure–Function Relationship Studies of Amphiphilic Small‐Molecule Ligands (Chem. Eur. J. 8/2018). Issue 8 (27th December 2017) - Okada, Yohei; Ishikawa, Kodai; Maeta, Naoya; Kamiya, Hidehiro
Abstract : Flexible colloidal stability : The cover picture shows a schematic impression of our synthesis approach toward nanoparticle‐ligand complexes with "flexible" colloidal stability. A series of amphiphilic small‐molecule ligands was synthesized with a special design principle. According to the design, well‐defined nanoparticle‐ligand complexes were then also fabricated. Thus, the nanoparticle–ligand complexes obtained showed flexible colloidal stability, namely, they were able to survive both under "dry (less‐polar)" and "wet (polar)" conditions. More information can be found in the Full Paper by Y. Okada et al. onpage 1853 .